GREEN LEARNING BASED ON SCL IN ANALYSING FOREST BIODIVERSITY TO INCREASE THE SKILL OF STUDENTS’ SCIENCE PROCESS OF FKIP UISU MEDAN - Nurhasnah Manurung (State Islamic University of North Sumatra Indonesia, 2020)
Before using SCL-based green learning the average level of science process skills of students or Pre Test = 23.19, after using Post Test = 65.33. Data analysis t count = 25.50> t table = 1.72 showed there was a significant increase in students' science process skills after using SCL-based green learning. For the lowest science process skills that is